Integration of GPS and low cost INS measurements - Hide, Christopher (2003)
GPS and Inertial Navigation Systems (INS) are increasingly used for positioning and attitude determination in a wide range of applications. Until recently, the very high cost of the INS components limited their use to high accuracy navigation and geo-referencing applications. Over the last few years, a number of low cost inertial sensors have come on the market. Although they exhibit large errors, GPS measurements can be used to correct the INS and sensor errors to provide high accuracy real-time navigation.